Pengaruh Pertumbuhan Penjualan, Perputaran Persediaan, Dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Di Masa Pandemi Covid-19 (Studi Kasus Pada Sub Sektor Ritel Yang Terdaftar Di Bursa Efek Indonesia) - Rita Syofyan; Aliffi Ibrahim (Universitas Negeri Padang, 2022)
This study aims to determine the effect of sales growth, inventory turnover and company size on profitability in retail sub-sector companies listed on the Indonesia Stock Exchange in 2020. The population in this study are retail sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling technique. Based on the criteria that have been set there are 23 companies. The type of data used is secondary data taken by accessing the website www.idx.co.id. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, it is known that the variables that partially affect profitability are sales growth with a significance value of 0.000 < 0.05, inventory turnover variable has no effect on profitability with a significance value of 0.693 > 0.05 and firm size variable has no effect on profitability. with a significance value of 0.085 > 0.05. Meanwhile, for simultaneous testing of the variables of sales growth, inventory turnover and company size affect profitability with a significance value of 0.000 <0.05. The magnitude of the influence of the independent variable on the dependent variable is 41.2%.Keywords : sales growth, inventory turnover, company size, profitability